Digital modelling on backwater effect due to bridge piers at Rasau river - Muhammad Shabirin, Sharom (2018)
Bridge is one of the important structures to connect two places usually separated by a river. Massive development occurs near the river area which resulted in increase in demand of river infrastructure such as bridge. A new bridge called Bridge 3 at Rasau River, Gambang is under construction to replace the existing bridge. Thus it is important to understand about the hydrology and hydraulic characteristic of the river to ensure the efficiency of the bridge’s design and its safety. One of the phenomena that can cause by the bridge piers is backwater. Backwater can cause a lot of environmental damages and, hence, it is crucial to consider the backwater effect even the bridge site at the Rasau River selected has stable banks and straight channel. In this study, HEC-RAS software was used to investigate the backwater effect through analysis of water profile. Simulations were carried out without and with the presence of the bridge piers. The result of the simulation showed in the form of water level versus station of the cross section. From this study, with the presence of bridge piers and 100-year ARI, the water level under the bridge had comply with the Guideline for River Development for having a water level of 11.18m from sea level and freeboard of 0.74m under the soffit of the bridge. Apart from that, overflows occurred at both the left and right of the river bank but not exceeded the road levels.